Identifying the inhibitory factors of dietary salt reduction in women: a qualitative study, Yazd, Iran. Issue 5 (1st December 2020) - Mazloomy Mahmoodabad, Seyed Saeed; Vaezi, Ali Akbar; Soltani, Tahere; Nadjarzadeh, Azadeh; Namayandeh, Seyedeh Mahdieh; Soltani, Mohammad Hossein; Fallahzadeh, Hossien
Abstract : Purpose: Increased dietary salt content is one of the effective factors of hypertension and a major public health challenge globally. Although the positive effects of dietary salt reduction on health are universally accepted, people can hardly reduce their salt intake. The purpose of this study is to identify the inhibitory factors of dietary salt reduction among 20–65-year-old women in Yazd City, Iran. Design/methodology/approach: This study was conducted using a deductive content analysis approach based on the communication for the behavioral impact (COMBI) framework. The purposeful sampling method was applied with maximum variation in terms of different educational levels, age groups, occupational status and residential areas to select the participants. Snowball sampling was used to select health-care professionals. Furthermore, semi-structured interviews and focus-group discussions were conducted with 31 local women and 11 health-care professionals working in the City until data saturation was achieved. Data were analyzed using Graneheim and Landsman's method. Findings: After data analysis, 617 initial codes were extracted over the perceived barriers. After merging similar codes, 223 codes were extracted. The barriers were classified into five main categories of family, personal, organizational, educational and socio-cultural barriers. Originality/value: Based on the COMBI framework, the results demonstrated that the most important barriers for reducing salt intake were negative attitude toward restrictions on dietary salt intake, insufficient and incorrect beliefs about the health risk of salt, lack of family support, inadequate health literacy and low self-efficacy in Yazd City. Among these barriers, lack of family support was considered as the most effective factor in reducing salt consumption. So, by focusing on this area and providing the community with the required education, the amount of salt consumed by families can be reduced.